If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2w + -3) * w = 14 Reorder the terms: (-3 + 2w) * w = 14 Reorder the terms for easier multiplication: w(-3 + 2w) = 14 (-3 * w + 2w * w) = 14 (-3w + 2w2) = 14 Solving -3w + 2w2 = 14 Solving for variable 'w'. Reorder the terms: -14 + -3w + 2w2 = 14 + -14 Combine like terms: 14 + -14 = 0 -14 + -3w + 2w2 = 0 Factor a trinomial. (-2 + -1w)(7 + -2w) = 0Subproblem 1
Set the factor '(-2 + -1w)' equal to zero and attempt to solve: Simplifying -2 + -1w = 0 Solving -2 + -1w = 0 Move all terms containing w to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + -1w = 0 + 2 Combine like terms: -2 + 2 = 0 0 + -1w = 0 + 2 -1w = 0 + 2 Combine like terms: 0 + 2 = 2 -1w = 2 Divide each side by '-1'. w = -2 Simplifying w = -2Subproblem 2
Set the factor '(7 + -2w)' equal to zero and attempt to solve: Simplifying 7 + -2w = 0 Solving 7 + -2w = 0 Move all terms containing w to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -2w = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -2w = 0 + -7 -2w = 0 + -7 Combine like terms: 0 + -7 = -7 -2w = -7 Divide each side by '-2'. w = 3.5 Simplifying w = 3.5Solution
w = {-2, 3.5}
| -456=n-385 | | -18=u-11 | | 4x=y+21-2x | | 5-3n=7n+80 | | 4(x+5)=-3(2x+10) | | (7+9t)(-2)+3(-5+4k)= | | 100-24= | | 28x^3k^2w^2-36x^2k^4y+42x^3k^4-24x^2k^2yw^2=0 | | 2x^3+4x^2-18x-16=0 | | -83=7x+4(2x+13) | | 16(x-16)=512 | | 7n+2=4(n+1) | | 2x^4+3x^3-6x^2-6x+4=0 | | -2x+5(4x+4)=128 | | 3(x+4)=3x+13 | | (3w+11)w=70 | | k-245=-184 | | r-5=-6 | | 2(x+2)=11 | | -6-4(x+7)=22 | | 6x+5x+3+7=7x+4+3x | | x^3=-16x | | 45x^2-24x+32=0 | | 4x-5x*2=33 | | 3(c-2)-3=-15 | | 4x+2=5y+1 | | -3x-x+3=-5 | | 10x+7.5y=420 | | 8x-17=5x+13 | | h=-36t^2+gt+d | | y-8=-6(x+1) | | 4eX=20 |